Testing new physics in long baseline neutrino oscillation experiments - Díaz Desposorio, Félix Napoleón (2022)
In this thesis, we focus on analyzing the different ways in which new physics scenarios, such as Violation of the Equivalence Principle (VEP) and Quantum Decoherence, can manifest themselves in the context of the neutrino oscillation phenomenon. Within the framework of the DUNE experiment, we examine several effects of the VEP, such as the possibility of getting a misconstructed neutrino oscillation parameter region provoked by our ignorance of VEP in nature, as well as the impact on the DUNE sensitivity for CPV and mass hierarchy. Additionally, we set limits for the different textures of the gravitational matrix and the diverse scenarios of energy dependencies associated with the Lorentz Violation. On the other hand, we demonstrate that the quantum decoherence phenomenon applied to the neutrino system leads us to fascinating phenomenological scenarios. One of the scenarios analyzed, within the context of quantum decoherence, is the one that breaks the fundamental CPT symmetry. For the latter, we identify what textures that include certain nondiagonal elements of the decoherence matrix are necessary. In this line, we propose a way to measure the CPT violation in the DUNE experiment using the muon neutrino and antineutrino channels for different energy dependencies. Another intriguing effect of considering the neutrino as an open quantum system is the possibility of discovering the neutrino nature by measuring the Majorana phase at the DUNE experiment achieving a competitive precision. As a consequence of the latter, we find that the crucial measurement of the CP violation phase (δCP), planned to be performed at the DUNE experiment, can be spoiled by the introduction of the decoherence and the Majorana phases in nature. Thus, a signature of a non-null Majorana phase is a sizable distortion in the measurement of the Dirac CP violation phase δCP at DUNE when compared with T2HK measurement. Subsequently, via simulation, we measured the Majorana phase for values of ϕ1/π = ±0.5 and decoherence parameter Γ = 4.5(5.5) × 10−24GeV, reaching a precision of 23 (21) %. This precision is consistent with the corresponding to the Dirac CP phase at T2K experiment.